The Economics of Data, Analytics, and Digital Transformation The Theorems, Laws, and Empowerments to Guide Your Organization's Digital Transformation. - Schmarzo, Bill (Packt Publishing, Limited, 2020)
A comprehensive guide for seasoned business leaders who struggle with where and how to exploit the economics of data and analytics to gain true value from data, accelerate company operations through AI, and guide their digital transformation.